2012
DOI: 10.1111/j.1467-9922.2012.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Success in Native and Non‐Native Listening Comprehension: An Individual Differences Approach

Abstract: The goal of this study was to explain individual differences in both native and non‐native listening comprehension; 121 native and 113 non‐native speakers of Dutch were tested on various linguistic and nonlinguistic cognitive skills thought to underlie listening comprehension. Structural equation modeling was used to identify the predictors of individual differences in listening comprehension and to test for differences between the native and non‐native participants. Listening comprehension for native speakers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
201
11
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(241 citation statements)
references
References 57 publications
(69 reference statements)
20
201
11
3
Order By: Relevance
“…The study reported here is part of a research project aiming at explaining individual differences between and within native and non-native speakers of Dutch in performing a listening comprehension task in Dutch. The explanation of individual differences in listening comprehension is sought in participant characteristics such as age, level of education, non-verbal intelligence and WM capacity, and in performance on a range of verbal tasks (one of which was a Dutch vocabulary-size task) (Andringa, Olsthoorn, van Beuningen, Schoonen, & Hulstijn, 2012). Thus, one important question in the project was which type of WM task we should best use to predict individual differences in listening comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported here is part of a research project aiming at explaining individual differences between and within native and non-native speakers of Dutch in performing a listening comprehension task in Dutch. The explanation of individual differences in listening comprehension is sought in participant characteristics such as age, level of education, non-verbal intelligence and WM capacity, and in performance on a range of verbal tasks (one of which was a Dutch vocabulary-size task) (Andringa, Olsthoorn, van Beuningen, Schoonen, & Hulstijn, 2012). Thus, one important question in the project was which type of WM task we should best use to predict individual differences in listening comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Vocabulary A vocabulary test in the form of multiple choice questions was administered to obtain a measure of linguistic knowledge (Andringa et al, 2012). The computerized test was administered in Excel (Courier font size 15).…”
Section: Linguistic Measuresmentioning
confidence: 99%
“…This paper reports on data collected in the framework of a larger, NWO-funded project, called Studies in Listening (StiLis), in which 345 people took part (235 native speakers [NS] and 110 non-native speakers of Dutch), who were tested on a large number of tests (Andringa, Olsthoorn, Van Beuningen, Schoonen, & Hulstijn, 2012). 1 The present study is restricted to an examination of the performance of the participants in the speech-segmentation task as affected, on the one hand, by participant variables (age, level of education [LoE], nonverbal intelligence, working-memory capacity [digit span], and reaction time in a nonverbal task) and on the other hand by stimulus characteristics (stimulus length and reduction of articulation).…”
Section: Methodsmentioning
confidence: 99%
“…The focus of the project (Andringa et al, 2012) of which the study reported in this paper is a minor part, was concerned with the associations between higher-order listening comprehension on the one hand and, on the other hand, lexical knowledge, accuracy and speed of verbal-information processing, working-memory capacity and non-verbal intelligence. This is the main reason why no hearing test was administered, given that subjects were using headsets and were allowed to adjust the volume to their convenience in all listening tasks.…”
Section: The Dictation Taskmentioning
confidence: 99%
See 1 more Smart Citation